Original articleExhaled nitric oxide correlates with IL-2, MCP-1, PDGF-BB and TIMP-2 in exhaled breath condensate of children with refractory asthma - Brzozowska, Agnieszka; Majak, Paweł; Jerzyńska, Joanna; Smejda, Katarzyna; Bobrowska-Korzeniowska, Monika; Stelmach, Włodzimierz; Koczkowska, Magdalena; Stelmach, Iwona (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : There is evidence that parameters obtained from exhaled breath condensate (EBC) reflect changes in the level of the airway lining fluid. The telation between exhaled nitric oxide (NO) and EBC inflammatory markers has not been analyzed in the context of the inflammatory profile in the airways in asthmatic children. Aim: To show the cytokine profile in EBC of children with severe/refractory asthma as well as correlations between the fractional exhaled NO (FeNO) level and cytokine concentrations. Material and methods : The study population consisted of eight children aged 8 to 17 years with IgE-dependent, severe/refractory asthma with a duration of at least 2 years. This was an observational study, the first consecutive eight patients with asthma symptoms on the day of the study visit, when EBC samples were obtained. Results: The inter-subject variability of study cytokines ranged from 8.6 to 54.6. Cytokines with coefficient of variation < 20% were: interferon-γ, interleukins IL-2, IL-7, IL-15, IL-16, monokine induced by interferon γ (MIG) and tumor necrosis factor α. We showed a significant positive correlation between the FeNO level and crucial mediators in asthma development and progression (IL-2, MCP-1), and potent markers of airway remodeling (PDGFBB, TIMP-2). All correlations between two different variables were controlled for the effects of age, forced expiratory volume in 1 s and number of asthma exacerbations during last 12 months. Conclusions : The profiling of cytokine expression in EBC can be reproducibly performed in children with severe/refractory asthma. When treating asthma in children, the FeNO level should be monitored as a prevention strategy of the progression of the remodeling leading to refractory/severe asthma. Exhaled breath condensate may be a useful tool to phenotype asthma via a non-invasive approach.